THE LEGAL PROTECTION AGAINST TERRORISM SUSPECTS IN INDONESIA (CASE STUDY OF THE ARREST PROCESS OF TERRORISM SUSPECTS BY DENSUS 88) - Sholahuddin Al-Fatih; Zaka Firma Aditya (Faculty of Law, University of Muhammadiyah Malang, 2019)
Terrorism is a form of extraordinary crime that not only leads to lives and material losses, but also creates a continuing fear in society. Backed by the many cases of terrorism with suicide bombing mode, especially in the case of Bali Bombing 1 and 2, then born special datachment 88 (Densus 88) which has the obligation to combat terrorism. Unfortunately, in cracking down on the perpetrators of terror, even those still suspected as terrorist suspects, Densus 88 often uses violence and even shoots off on the spot. The late Siyono was one of the victims of repressive measures carried out by Densus 88. In other cases, Densus 88 is also often proven to mis-arrest after the suspect has lost his life. This condition is certainly contrary to the spirit of democracy and efforts to guarantee human rights protection in Indonesia. This paper discusses: (1) the Standard Operational Procedure of terrorist suspected arrest process by Densus 88 and its comparison with anti terrorism agency in other country; and (2) Guarantees and legal protection in the fulfillment of the rights of suspected terrorists.